Rational design of stable and functional hirudin III mutants with lower antigenicity. Issue 6 (November 2015) - Asgari, Saeme; Mirzahoseini, Hasan; Karimipour, Morteza; Rahimi, Hamze; Ebrahim-Habibi, Azadeh
Abstract: Hirudin is an inhibitor of thrombin and used as an effective anticoagulant, but has a potential to develop unacceptable immune responses. In this study, two computational tools were used to predict T-cell epitopes within Hirudin variant III (HVIII) sequence, and design mutations that would lessen its antigenicity. Homology models of native and mutant HVIII proteins (T4K, S9G, V21G, and V21K) were generated, and further used to assess their interactions with thrombin. The docking experiment showed that all mutants had a suitable pattern of interactions, with similar or lower interaction energies compared with the native protein. These complexes were subsequently subjected to molecular dynamics simulation. All mutants complexes had overall stable structures over simulation time, with RMSD, gyration radius, hydrogen bonds numbers, and accessible surface areas patterns that were comparable with the native HVIII over time. Interestingly, in all mutants, a shorter length was observed for the two salt bridges Arg73-Asp55 and Arg77-Glu57, which are suggested to be important in Hirudin-thrombin complex formation. Best selected mutants expressed in Escherichia coli BL21(DE3), subsequently SDS-PAGE and Western blot analysis confirmed the successful same expression of Hirudin and mutants. In conclusion, we believe that this computational approach could identify potentially safer proteins with preserved or even improved functionality. Highlights: Hirudin: anticoagulant and inhibitor of thrombin causing unwanted immune responses. In silico identification and removing of T-cell epitopes from Hirudin. Testing mutated candidates T4K, S9G, V21G and V21K by molecular dynamics simulation. All mutants: stable and functional comparable with or better than native Hirudin.